2003
DOI: 10.1103/physrevlett.91.264301
|View full text |Cite
|
Sign up to set email alerts
|

Superstable Granular Heap in a Thin Channel

Abstract: We observed experimentally a new regime for granular flows in an inclined channel with a flow-rate-controlled system. For high flow rates, the flow occurs atop a static granular heap whose angle is considerably higher than those usually exhibited by granular heaps. The properties of such superstable heaps (SSH) are drastically affected by a change in the channel width W. This indicates that the unusual stability of these heaps can be accounted for by the flowing layer and its friction on the sidewalls. A simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

31
235
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(268 citation statements)
references
References 20 publications
31
235
2
Order By: Relevance
“…Nearly the same characteristic length of the exponential tail is observed in [10] with, above this transition region of the velocity profile, a linear part that progressively extends in depth up to a maximal flow thickness. It has been shown that the size of this flowing layer is governed by the channel width and the friction on the sidewalls [13,30,32]. In [11], it appears that the avalanche duration is too small for the linear part to be observed in the velocity profile.…”
Section: Comparison and Discussion On Velocity Profilesmentioning
confidence: 99%
See 3 more Smart Citations
“…Nearly the same characteristic length of the exponential tail is observed in [10] with, above this transition region of the velocity profile, a linear part that progressively extends in depth up to a maximal flow thickness. It has been shown that the size of this flowing layer is governed by the channel width and the friction on the sidewalls [13,30,32]. In [11], it appears that the avalanche duration is too small for the linear part to be observed in the velocity profile.…”
Section: Comparison and Discussion On Velocity Profilesmentioning
confidence: 99%
“…[10,11,13,[28][29][30]. To compare and discuss more in details those velocity profiles, we will first refer to the work carried out by Courrech du Pont et al [14] who have defined three flow regimes for a granular avalanche in a fluid based on the fall under gravity of one grain in fluid: a free fall regime for which there is no fluid influence (i.e.…”
Section: Comparison and Discussion On Velocity Profilesmentioning
confidence: 99%
See 2 more Smart Citations
“…Granular materials persist at the forefront of contemporary research due to the extreme richness in their dynamics, either under shear [1], flowing out of a hopper [2], or driven by gravity [3]. Because thermodynamic temperature plays little role in determining these features, granular materials are widely recognized as a macroscopic analogue of athermal systems far from equilibrium [4].…”
mentioning
confidence: 99%